Zero-dimensional modelling of a four-cylinder turbocharged diesel engine with variable compression ratio and its effects on emissions - GÜL, MEHMET ZAFER (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
With emission legislation becoming ever more stringent, declining fossil resources and an increase in greenhouse effect caused by CO2 emissions, manufacturers are exploring new ways to match the emissions regulations without compromising on the performance of the engine. This study included development of zero-dimensional model of a 2.0 L turbocharged diesel engine and then study the effects of changing its compression ratio in the numerical model. This paper gave a framework in determining the effect of compression ratios in different operational conditions of the engine. Implementation of variable compression ratio technology on a numerical model proved to be very cost-effective, time saving and validated the fact that numerical models can be used to study different parameters of the engines during the development stage. The main effect of an increase in compression ratio, was found to be as expected, a decrease in brake specific fuel consumption and an increase in thermal efficiency with a greater impact at low rpm-low load regions. Assuming, that the variable compression ratio technology can be utilized in the engine, this work found the best combination of compression ratios around the engine map, giving a best fit of trade-offs between the emissions and performance of the engine. This study also validates the fact that variable compression ratio technology, if implemented in the engine could not only reduce emissions of the engine but can be given as an option to the end-user to switch to more economic fuel consumption values during idling or cruising at long distant journeys.
Keywords: Internal combustion engine; Variable compression ratio; Numerical modelling; Combustion; Emissions; Zero dimensional